An analytical approach to assess the influence of the massive wall material, thickness and ventilation system on the Trombe wall thermal performance - Briga Sá, Ana Cristina (2019)
The influence of the massive wall material, thickness and ventilation system on the Trombe wall thermal performance was analysed based on an analytical methodology. Results obtained from experimental work will also be added to this study. During the heating season, for the non-ventilated Trombe wall, the global heat gains decrease is not proportional to the thickness increase, and this ratio depends on the massive wall material heat storage capacity. A ventilation system in the massive wall leads to higher heat gains due to the air convection, but this growth is not in the same proportion for the different materials. If solid brick or earth is used, heat gain values are much higher than those obtained if there is no ventilation system, increasing to the double in the case of earth and 2.5 times more in the case of solid brick. When the massive wall is ventilated and made of granite, an increase in the gains of 44.06% is obtained when compared with the non-ventilated. During the cooling season, closing the ventilation system and the external shutter leads to heat gains considerably lower than those obtained during the heating season. In this case, earth can be a suitable material.